2009
DOI: 10.1053/j.ajkd.2009.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Nephrotic Syndrome and Atopy: Is There a Common Link?

Abstract: Numerous reports during the last 60 years have reported a strong association between idiopathic nephrotic syndrome and atopic disorders. Idiopathic nephrotic syndrome can be precipitated by allergic reactions and has been associated with both aeroallergens (pollens, mold, and dust) and food allergies. Patients with idiopathic nephrotic syndrome also may show increased serum immunoglobulin E (IgE) levels. A review of the literature suggests that although some idiopathic nephrotic syndrome cases may be associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
119
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 58 publications
2
119
1
2
Order By: Relevance
“…2,3 In many studies, increased incidence of allergic diseases and high serum IgE levels have been reported in SSNS. 2,[4][5][6]9,[16][17][18][19] These findings support the existence of a dysfunction of the humoral immune response in the nephrotic syndrome. 4,6,7,18,19 The term ''atopy'' is used to define IgE-mediated diseases.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…2,3 In many studies, increased incidence of allergic diseases and high serum IgE levels have been reported in SSNS. 2,[4][5][6]9,[16][17][18][19] These findings support the existence of a dysfunction of the humoral immune response in the nephrotic syndrome. 4,6,7,18,19 The term ''atopy'' is used to define IgE-mediated diseases.…”
Section: Discussionmentioning
confidence: 55%
“…As it has been stated in the past, the belief today too is that the immune system plays an important role in this condition. [5][6][7][8][9] In particular, there is strong evidence pointing to T-cell disorder mediated by a circulating factor that creates podocyte dysfunction and massive proteinuria. 2,3 In many studies, increased incidence of allergic diseases and high serum IgE levels have been reported in SSNS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations